Cognitive abilities underlying performance on the modified card sorting test: novel and traditional scores. Issue 5 (3rd September 2021) - Branco, Laura Damiani; Cotrena, Charles; Shansis, Flávio Milman; Fonseca, Rochele Paz
Abstract: The Modified Card Sorting Test (MCST) is a widely used variation of the Wisconsin Card Sorting Test. It is faster to administer, less frustrating for respondents and less ambiguous in its scoring but has been criticized for its task impurity and low discriminability between control participants and clinical groups prone to executive dysfunction. This study aimed to examine the executive functions (EF) underlying traditional (number of categories completed, perseverative errors) and novel scores for the MCST, and compare their ability to differentiate between control and clinical samples. Novel and traditional MCST scores were compared between 94 control participants, 87 with bipolar disorder and 64 with major depression. The relationship between MCST scores and traditional EF tasks was examined through correlation and regression analyses. All MCST scores were associated with at least one measure of EF, the most common of which were the Trail Making or Hayling Tests. IQ predicted most scores on the MCST, save for nonperseverative errors and categorizing efficiency. Traditional and novel scores differentiated between clinical and control groups. These findings support the utility of the MCST in detecting executive dysfunction and highlight the importance of new scoring methods in increasing the specificity and interpretability of this task.